Javanese (Indonesia) indigenous education in a children’s literature novel at Vorstenlanden in 1937 - Apri Damai Sagita Krissandi; Andayani Andayani; Atikah Anindyarini (Cogent Education, 2023)
AbstractStudies on indigenous education have become popular in recent years. In Indonesia, indigenous education studies are carried out to rediscover a distinctive educational identity. This study aims to describe the indigenous education of children in Java during the Dutch colonial period through a study of children’s literary novels in Vorstenlanden in 1937. This is a qualitative study. The novel under study is titled Bocah Mangkunegaran which is a children’s literary novel by a well-known author at that time, namely Jasawidagda. This novel was chosen because of its journalistic style which combines historical facts with fiction. This novel records events in the colonial era from the point of view of indigenous children who are educated with indigenous education. The results of the study show that indigenous education is one of the efforts of the Javanese people to resist colonialism, western education models, and priyayi social class. Indigenous education for Javanese children emphasizes feeling, soul and character, not just logic and reason. Indigenous education covers: 1) Economic education for non-priyayi people; 2) Character education and schooling for Javanese children; 3) Education on Javanese religiosity (kejawen), mythology, and puppets; 4) Regional education; and 5) Scouting education (padvinder).